The 1961 vienna convention implementations on eradicating structural discrimination of diplomatic corps towards the protection of female diplomats rights - Serera, Aulia Yuti; Azzaulfa, Anisa; Anhari, Radifan; Riandy, Ervin (Priviet Social Sciences Journal, 2026)
The role of female diplomats on the international stage has increased significantly over the last two decades. However, the role of female diplomats remains limited in some areas, such as human rights, international peace, and climate change. They also play a limited role as negotiators, facilitators, and policy designers. This condition leads to the structural discrimination faced by female diplomats. The 1961 Vienna Convention on Diplomatic Relations (VCDR) was formulated to grant all diplomats, including female diplomats, the protection of diplomatic functions and the official status of diplomats. This research adopts a normative-empirical approach to analyze how the implementation of the 1961 VCDR eradicates the structural discrimination of the diplomatic corps towards the protection of the rights of female diplomats. The research findings show that women’s involvement in diplomacy still faces a significant gap in terms of numbers and levels assigned. Female diplomats also face the risk of gender violation and harassment. The 1961 VCDR was formulated as a gender-neutral foundation for diplomatic protection, which means it lacks specific provisions on gender-based discrimination or violence. Consequently, addressing issues such as unequal postings and promotions heavily relies on national policies, labor laws, and international human rights instruments such as CEDAW, rather than the 1961 VCDR directly. The empowerment of female diplomats requires a multi-faceted approach involving both normative efforts and structural reforms.